1998
DOI: 10.1590/s0074-02761998000100016
|View full text |Cite
|
Sign up to set email alerts
|

The Preimaginal Stages of Cryptotylus unicolor (Wiedemann) and Tabanus nebulosus ornativentris Kroeber (Tabanidae-Diptera-Insecta)

Abstract: A larva with peculiar very long pubescence on the integument, the pupa of Cryptotylus unicolor, and the larva and pupa of Tabanus nebulosus ornativentris are described and illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…The immature morphology of some families have been used for phylogenetic studies in mosquitoes (Diptera: Culicidae) (Harbach & Peyton 1993), black flies (Diptera: Simuliidae) (Py-Daniel & Moreira Sampaio 1994) and horseflies (Diptera: Tabanidae) (Coscarón et al 1998). From these studies, it seems that the appearance of the phlebotomine larvae antennae might be a constant character among species of the same subgenus or spe-cies group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immature morphology of some families have been used for phylogenetic studies in mosquitoes (Diptera: Culicidae) (Harbach & Peyton 1993), black flies (Diptera: Simuliidae) (Py-Daniel & Moreira Sampaio 1994) and horseflies (Diptera: Tabanidae) (Coscarón et al 1998). From these studies, it seems that the appearance of the phlebotomine larvae antennae might be a constant character among species of the same subgenus or spe-cies group.…”
Section: Discussionmentioning
confidence: 99%
“…Williams (1996, 1997) mentioned probable sensillae on the integument, antennae and mouth structures of L. longipalpis. Coscarón et al (1998) also observed sensory structures in larvae of Tabanidae with SEM.…”
mentioning
confidence: 86%
“…Gorayeb and Fairchild provided a new key for the genus and described Cryptotylus firkin Gorayeb and Fairchild, from Amazonian subregion, province of Para [127]. Coscarón and collaborators collected larvae of Cryptotylus unicolor (Coscarón and Poi of Neif) on Pistia stratiotes Linnaeus, in ponds in a region of dry forest, northeastern Argentine, province of Formosa, Argentine Chaco [128].…”
Section: Genus Chlorotabanusmentioning
confidence: 99%
“…In addition to describing various species of several genera, Coscarón revised genera Dicladocera Lutz in Argentina [141] and Lepiselaga Macquart [227], the subgenus Mesomyia (Coracella) Philip [47], genera Dichelacera Macquart [214], Stenotabanus Lutz and Myiotabanus Lutz [161], Catachlorops Lutz [114], Leucotabanus Lutz, Pseudacanthocera Lutz, Bolbodimyia Bigot and Pachyschelomyia Barretto [228], Diachlorus Osten Sacken, Stibasoma Schiner, Stypommisa Enderlein, Cryptotylus Lutz and Chlorotabanus Lutz [229], Tabanus Linnaeus [173], Chrysops Meigen [230], Phaeotabanus Lutz and Acanthocera Macquart [231], Scione Walker [88], Fidena Walker [91], Poeciloderas Lutz [171], the subgenus Scaptia (Lepmia) Fairchild [232], the genus Dasybasis Macquart [130], the tribe Mycteromyiini [68], and the subgenus Scaptia (Scaptia) Walker [233]. He also studied the immature stages of several species in several genera [85,128,132,133,149,[234][235][236][237]. In 2002, Coscarón compiled an illustrate key to larvae and pupae of Argentine tabanids [238]; and in 2014, Coscarón and Papavero published another more elaborated key to tabanids immature stages of Neotropical tabanids [239].…”
Section: Appendixmentioning
confidence: 99%
“…Entretanto, maior aporte foi fornecido por Goodwin & Murdoch (1974) com ilustrações e chaves de 15 gêneros de larvas e 17 de pupas. Dados biológicos e morfológicos foram reunidos nos trabalhos de Coscarón (1969), Coscarón & Philip (1967), Coscarón & Led (1969), Coscarón & González (1989), Coscarón (1991), Coscarón et al (1996), Coscarón et al (1998), Coscarón (1999) e, mais recentemente, descreveram uma espécie nova a partir de exúvia pupal. Diferentes sistemas aquáticos são mencionados como criadouros.…”
unclassified